Teachers’ Challenges in Teaching English Pronunciation (A Case Study at One of the Senior High Schools in Ciamis) - Alya Handaya Putri; Didih Faridah; Rina Herlina (Universitas Galuh, 2026)
Pronunciation is a crucial component of English communicative competence and plays a vital role in ensuring intelligibility in spoken interaction. In the Indonesian EFL context, teaching pronunciation remains challenging due to limited exposure to authentic language, mother-tongue interference, and insufficient resources. Despite previous studies on pronunciation pedagogy, research integrating the psychological, linguistic, and pedagogical dimensions of teachers’ challenges, particularly at the high school level, remains limited. The present study aims to investigate the obstacles EFL teachers face in teaching pronunciation and to identify the strategies the EFL students employ to address these obstacles. This research uses a qualitative case study involving three EFL teachers in a senior high school in Ciamis, Indonesia. Data were gathered through classroom observations and semi-structured interviews, then analysed using thematic analysis. The findings reveal five primary challenges: low student self-confidence, limited time and resources, difficulties in linking spelling and pronunciation, first-language interference, and inconsistent practice. Teachers addressed these constraints through ice-breaking activities, contextualised repetition, constructive feedback, bilingual explanations, and materials connected to students’ interests. The study concludes that effective pronunciation instruction requires balancing technical accuracy with affective support, providing consistent practice opportunities, and adopting adaptive strategies tailored to learners’ needs. Overall, the findings emphasise that addressing both cognitive and emotional factors is essential for enhancing pronunciation learning in the EFL classroom.